Preliminary study on the micropropagation in vitro of black pepper (Piper nigrum L.) - Thuyen, Doan Ai; Du, Thai Xuan; Giap, Do Dang; Ton, Nguyen Tang (Academia Journal of Biology, 2014)
The plant regeneration from the single node or the callus culture of black pepper (Piper nigrum L.) was described. Various combinations of media, growth regulators and explant sterization were compared. Problems, probably caused by endogenous pathogens associated with tissue exudated, often occurred during the establishment of culture. The method to sterilize the black pepper plants using antibiotic agent such as cefotaxin was described. For the shoot initiation and the establishment, the optimal concentration of black pepper growth was BA 2mg/l, IBA 0.5 mg/l. The high concentrations of BA (5-10 mg/l) had no effect on the shoot regeneration from callus and the development of lateral branches. The MS medium containing BA 5.0 mg/l, Kin 0.5 mg/l and IBA 0.5 mg/l was the best medium for the subsequent growth and the shoot regeneration from callus under the current condition. Shoots were rooted on 1/2 MS medium containing NAA 0.1-0.2 mg/l. In vitro plants were then transferred to pots in the nursery house. After 8-10 weeks, the plants with height of 20-25 cm were transferred to field for testing.